The present situation of the nursing practice environment and its influence on nursing quality in a post-epidemic era: a cross-sectional study - Xiaotong Liu; Yabin Guo; Yang Zhou; Yang Zhou (BMC, 2024)
Abstract Background Nursing Practice Environment is an important index to improve nursing quality and patient outcome. To explore the nursing practice environment in the COVID-19 ward during the period of COVID-19 and its impact on nursing quality to provide reference for setting up supporting nursing team in epidemic area in the future. Methods A cross-sectional survey was conducted among 251 nurses working in COVID-19 ward in Shanghai, Hainan and Hunan in December 2022 through stratified proportional sampling. Structured questionnaires, including general information questionnaire, professional practice environment scale and nursing quality questionnaire, were used to investigate the patients. Pearson correlation was used to analyze the correlation between nursing practice environment and nursing quality, and multiple linear regression analysis was used to analyze the influencing factors of nursing quality in the COVID-19 ward. Results The professional practice environment scale score was (3.34 ± 0.40), the nursing quality questionnaire score was (9.47 ± 0.81), both at a high level. Single factor analysis showed that nursing quality was related to educational background, physical condition, professional title, grade of the original hospital and composition of nursing staff in supported departments. Nursing quality were positively correlated with each nursing practice environment dimensions (in addition to teamwork). The results of regression analysis showed that the nursing practice environment in the COVID-19 ward had a positive impact on nursing quality. Conclusions The nursing practice environment and nursing quality of nurses in the COVID-19ward is generally very high. The education, working hospital level and nursing practice environment of nurses are the important factors influencing nursing quality. The relationship between nursing practice environment (include leadership and autonomy in clinical practice, staff relationships with physicians, control over practice, communication about patients, handling disagreement and conflict, internal work motivation and cultural sensitivity) and nursing quality is positive. It is suggested that the hospital should pay special attention to and improve nursing practice environment in order to improve nursing quality when setting up temporary ward in the future epidemic period of infectious diseases, ensure patient safety. Impact on clinical practice Research shows that an active nursing practice environment can improve the quality of care, and nursing managers create and maintain an active practice environment to improve the quality of care and ensure patient safety.